Application of the input-output model for structural analysis on the example of the agricultural sector in Poland = Zastosowanie modelu input-output do analiz strukturalnych na przykładzie sektora rolnego w Polsce - Czyżewski, Andrzej; Grzelak, Aleksander (Zielona Góra: Faculty of Economics and Management Press)
The main objective of the article is to recognize possibilities of use of the input-output model to structural assessments in the economy, with particular reference to the agricultural sector. The included considerations have a theoretical and application dimension related to the agricultural sector. Understanding the nature of structural changes and associated tendencies is particularly useful in shaping the economic policy of the state about the use of non-automatic economic stabilizers and the identification of areas that constitute development barriers.
Keywords: przepływy międzygałęziowe; gospodarka; rolnictwo; analizy strukturalne; input-output; economy; agriculture; structural analysis